The Impact of Tax Policy on Investment Decisions: A Case Study in the Manufacturing Industry - Rely, Gilbert (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
This research delves into the intricate relationship between tax policy and investment decisions within the manufacturing industry. Through a comprehensive literature review, the study aims to elucidate the impact of tax incentives on investment behavior, particularly focusing on their effectiveness in stimulating innovation and competitiveness among manufacturing firms. Employing qualitative research methodology, the selection of literature involves identifying and analyzing scholarly articles, books, and reports that provide insights into the research topic. Data collection entails systematic gathering of information from selected sources, while data analysis involves identifying themes, patterns, and relationships within the literature. The findings underscore the pivotal role of tax incentives, such as investment tax credits, accelerated depreciation, and research and development (R&D) deductions, in shaping investment decisions within the manufacturing sector. Moreover, the differential effects of tax policy reforms on firms of different sizes, the influence of global dynamics including international tax competition and trade liberalization, and the implications for future research are discussed. The study contributes to a deeper understanding of the mechanisms through which tax policy influences investment decisions, offering insights for policymakers and businesses to navigate the complexities of the global economy more effectively.